2021
DOI: 10.21203/rs.3.rs-123645/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Subcutaneous Adipose Tissue Cell-derived Cytokines Are Early Markers of Impaired Glucose Tolerance in Severe Obesity

Abstract: Background Excessive adiposity provides an inflammatory environment. However, in people with severe obesity, how systemic and local adipose tissue (AT)-derived cytokines contribute to worsening glucose tolerance is not clear. Methods 92 severely obese (SO) individuals undergoing bariatric surgery were enrolled and subjected to detailed clinical phenotyping. Following an Oral Glucose Tolerance Test, participants were included in three groups, based on the presence of normal glucose tolerance (NGT), impaired g… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
(62 reference statements)
0
3
0
Order By: Relevance
“…The BMI has the heaviest impact on the correlation between LGCI-related risk factors and cytokines. Indeed, many studies have characterized the cytokine profile in subjects with obesity and/or severe obesity detecting differences compared with normal weight individuals (10,27,28). In this study, we have found that, despite the removal from the analysis of subjects with obesity, BMI was still significantly associated with CRP levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The BMI has the heaviest impact on the correlation between LGCI-related risk factors and cytokines. Indeed, many studies have characterized the cytokine profile in subjects with obesity and/or severe obesity detecting differences compared with normal weight individuals (10,27,28). In this study, we have found that, despite the removal from the analysis of subjects with obesity, BMI was still significantly associated with CRP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity drives the pathological expansion of the adipose tissue, which harbors enlarged hypertrophic adipocytes, impaired vasculogenesis, and enhanced fibrosis and hypoxia. Dysfunctional adipose tissue secretes pro-inflammatory cytokines that promote local and systemic inflammation, contributing to the onset of obesity-related diseases (8)(9)(10). The loosening of the cytokine balance between the pro-inflammatory and anti-inflammatory control is a characteristic feature also of aging.…”
Section: Introductionmentioning
confidence: 99%
“…Still, here we aimed to identify specific associations of DII with psychological domains strictly related to depressive symptoms, which prompted us to perform sensitivity analyses adjusting for resilience. Similarly, adiposity may play a mediator role since it can be clearly influenced by fat-rich (proinflammatory) diets and adipose tissues contribute to the secretion of inflammatory cytokines, 37 hence we included RFM adjustment in sensitivity models to detect potential fat-independent associations. A detailed description of these variables is reported in Supplementary Methods.…”
Section: Statistical Analysesmentioning
confidence: 99%